An Analysis of Georgia Hybrid Program Characteristics and Hybrid Homeschool Student Academic Achievement - Masinelli, Sharon (My University, 2024)
As homeschooling numbers rose following the COVID-19 pandemic,nontraditional education such as hybrid homeschooling was reported as a desirable option by parents. This dissertation examines the academic outcomes of homeschool and hybrid homeschool students in Georgia following the rise of post-COVID nontraditional education. Hybrid homeschooling, a blend of homeschooling and private education, has grown in popularity and yet the impact on student achievement remains largely unexplored. This study analyzes SAT performance among homeschool and hybrid homeschool students, comparing it to public and private school averages using a quantitative methodology. A series of t-tests, ANOVAs, and ultimately a multiple regression analysis was performed after administering an anonymous survey to Georgia hybrid homeschool families and homeschool families. Results indicate both homeschool and hybrid homeschool students scored significantly higher on the SAT than their public and private school counterparts. However, no significant difference was found between homeschool and hybrid homeschool students’ SAT scores. Further analysis of factors such as set schedules, parental assistance, days attended in hybrid programs, and hybrid program characteristics aligned to Epstein’s Theory of Parental Involvement revealed no significant predictive relationship with SAT scores.
Keywords: Education; Pedagogy; Dissertations, Academic--United States; Educational tests and measurements; Georgia; Home schooling; Correspondence schools and courses; Alternative education; Academic achievement; Hybrid learning; College entrance achievement tests; Education--Evaluation; COVID-19 Pandemic, 2020; Educational surveys; Education--Parent participation; Dissertations, Academic--United States; Quantitative research; Surveys